Response characteristics and mechanism for fracturing interference of adjacent wells of shale gas wells: A case study in the Fuling shale gas field - Jincai SHEN (地质科技通报, 2024)
Objective Regarding conventional gas resources, research on the fracturing interference of adjacent wells has focused mainly on interference during the production process; the interference of adjacent wells is usually avoided by determining the rational spacing between wells, and the radius of influence is the key to determining a reasonable well spacing. The fracturing interference of shale gas adjacent wells involves various types, phenomena, results and control factors; however, there is no generally accepted description method or mechanism for studying the response characteristics of the fracturing interference of adjacent wells. Methods The Fuling shale gas field is taken as an example to discuss the response characteristics and mechanism of the fracturing interference of adjacent wells in shale gas. Results According to the impact on the recoverable reserves of parent wells, the fracturing interference of shale gas adjacent wells can be divided into three types: positive interference, noninterference and negative interference. The three types of interference are mainly related to the spacing of the child and parent wells, crossing layers, recovery percentage, formation pressure, stress difference and other factors. The closer the spacing and crossing layers between wells are, the greater the recovery degree of the parent wells or the lower the formation pressure is, the greater the difference between both sides of the stress of the child well becomes, and the greater the fracturing interference becomes. On the basis of the different results caused by fracturing interference, to avoid negative effects, shale gas development requires the formulation of reasonable well spacings, the shuttling of parent wells to restore the pressure until it stabilizes before fracturing, and the use of diverters during fracturing of new child wells. The generation mechanisms of fracturing interference are the degree of fracture and the overlap of artificial fracturing networks between child wells and parent wells. The ideal situation is that the fracturing network edge of the child wells just reaches the fracturing network edge of the older parent wells, which has a positive effect on increasing production; however, the noninterference type does not occur when the child wells' SRV is insufficient, nor does the negative interference type occur when the fracturing networks are connected between the child wells and parent wells. Conclusion The research results provide theoretical support for formulating reasonable fracturing interference prevention measures and have good guiding significance in industry.